Determination of Bankruptcy Potential in Indonesian Transportation Companies After the COVID-19 Pandemic - Arifin, Farid (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This study examines the factors influencing bankruptcy risk among transportation companies after Covid-19 listed on the Indonesia Stock Exchange during 2017–2024 using the Grover model. The model serves as an early warning system by integrating financial ratios relevant to the transportation sector, including Total Asset Turnover, Current Ratio, and Debt-to-Equity Ratio. Secondary data were obtained from official financial reports published on the IDX website and company websites. The research employs purposive sampling, resulting in nine companies as the sample, and applies Panel Data Regression Analysis. Analytical procedures include descriptive and verification analysis, model selection, classical assumption testing, coefficient of determination, and hypothesis testing using t-tests and F-tests, processed with EViews 13. The descriptive results indicate significant fluctuations in TATO, CR, DER, and G-Score values during the study period. Empirical findings reveal that TATO has no significant effect on bankruptcy risk, CR has a significant negative effect, and DER has a significant positive effect on bankruptcy risk based on the Grover model. These findings highlight the importance of liquidity and leverage management in mitigating financial distress within the transportation sector.